1997
DOI: 10.1111/j.1349-7006.1997.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Magnesium in Drinking Water and Risk of Death from Colon Cancer

Abstract: The possible association between the risk of colon cancer and the levels of calcium and magnesium in drinking water from municipal supplies was investigated in a matched case‐control study in Taiwan. All eligible colon cancer deaths (1714 cases) of Taiwan residents from 1989 through 1993 were compared with deaths from other causes (1714 controls), and the levels of calcium and magnesium in drinking water of these residents were determined. Data on calcium and magnesium levels in drinking water throughout Taiwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 32 publications
0
49
2
Order By: Relevance
“…Another case-control study showed a moderate inverse association between magnesium 11 level in drinking water and prostate cancer mortality (58). However, the relationship for 12 magnesium intake from food has never been reported.…”
Section: Dietary Magnesium Intake 18mentioning
confidence: 96%
“…Another case-control study showed a moderate inverse association between magnesium 11 level in drinking water and prostate cancer mortality (58). However, the relationship for 12 magnesium intake from food has never been reported.…”
Section: Dietary Magnesium Intake 18mentioning
confidence: 96%
“…Thereafter, a considerable number of studies have been published investigating this general association in many different nations. Furthermore, recent studies have begun to examine more diverse health outcomes including cancer (Yang & Hung 1998;Yang et al , 2000Yang et al , 2002. The hardness of drinking water is directly determined by the concentration of dissolved minerals, predominantly calcium and magnesium, mainly in combination with bicarbonate, sulphate and chloride.…”
Section: Introductionmentioning
confidence: 99%
“…As, Cd, Pb). The latest clinical studies indicate that breast cancer (but also other carcinogenic diseases like cancer of prostate, digestive tract) could be associated partially also to the contents of macro-components in human tissues and fluids, mainly Ca and Mg [16][17][18][19]. The mortality from breast cancer is rather rough parameter, depending strongly on early diagnostics and effectiveness of administered therapy.…”
Section: Relative Mortality From Breast Cancer (C50)mentioning
confidence: 99%